2011
DOI: 10.1038/nm.2382
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacological approach to first aid treatment for snakebite

Abstract: Snake venom toxins first transit the lymphatic system before entering the bloodstream. Ointment containing a nitric oxide donor, which impedes the intrinsic lymphatic pump, prolonged lymph transit time in rats and humans and also increased rat survival time after injection of venom. This pharmacological approach should give snakebite victims more time to obtain medical care and antivenom treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 16 publications
(20 reference statements)
8
40
1
Order By: Relevance
“…It has recently been demonstrated that oxazolone-mediated inflammatory responses increase capillary permeability (9), spur inducible nitric oxide (NO) release (17), and reduce lymphatic flow (11). NO is a key molecular regulator of lymphatic contractility (1) that is known to slow lymphatic drainage by reducing lymphatic contraction (30,43). Reduced lymphatic pumping activity due to increased NO production may explain the appearance of edema in the ALND Ϫ oxazolone ϩ forelegs.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been demonstrated that oxazolone-mediated inflammatory responses increase capillary permeability (9), spur inducible nitric oxide (NO) release (17), and reduce lymphatic flow (11). NO is a key molecular regulator of lymphatic contractility (1) that is known to slow lymphatic drainage by reducing lymphatic contraction (30,43). Reduced lymphatic pumping activity due to increased NO production may explain the appearance of edema in the ALND Ϫ oxazolone ϩ forelegs.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment group received a topical application of a glyceryl trinitrate ointment (GTNO) (0.2% wt∕wt, Rectogesic, Care Pharmaceuticals, commercially available), which is an ointment with an NO donor group that has previously been reported to slow lymphatic transport time. 35 Fig . 2 Tissue phantom schematic and operation.…”
Section: In Vivo Imagingmentioning
confidence: 99%
“…Our findings, that GTNO significantly reduces lymphatic transport, corroborates existing knowledge that NO has an inhibitory effect on lymphatic pump function. 29,31,35 We have shown that NIR lymphatic imaging can provide real-time in vivo measurements of lymphatic pump function in response to NO, which has never previously been available, and may help to further elucidate the relationship between NO and lymphatic contractile regulatory mechanisms. The ability to measure this response non-invasively would be particularly useful given recent findings that certain immune cells migrate to the lymphatics and release NO as a means of regulating local lymphatic draining.…”
Section: Quantifying Functional Effects Of No On Lymphatics In Vivomentioning
confidence: 99%
“…The application of pressure-immobilization, by applying a bandage and a splint to the entire bitten limb, has been used in Australia for delaying the systemic absorption of neurotoxic venoms (Sutherland et al, 1979;White, 2010). Recently, a pharmacological intervention, based on the application of an ointment containing a nitric oxide donor, aimed at reducing the lymphatic absorption of venom, has been proposed (Saul et al, 2011), and its testing in the clinical setting is pending.…”
Section: First Aid In Snakebite Envenomingmentioning
confidence: 99%